1999
DOI: 10.1081/ma-100101612
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polypropylene Homopolymer in the Molten State in Presence of Air

Abstract: The oxidation of polypropylene (PP) homopolymer in air was performed using dodecanol-1 as an accelerator. The experiments were conducted under atmospheric pressure at 180-220 o C. Spectroscopic data indicated the formation of polar groups such as ketones, esters, alcohols, anhydrides etc. as determined by FTIR and ESCA. The scanning electron microscopy (SEM) showed the variations of morphology of the oxidation products. The fusion temperatures were determined by differential scanning calorimetry (DSC). The var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The oxidation of PP was realized according to the method described by Abdouss and Sharifi-Sanjani. 17 According to this method, first PP and dodecanol-1 were mixed in an internal mixer (Brabender, Duisburg, Germany). Dried, filtered air was then put in contact with the molten mass at a flow rate of 1 L/min.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation of PP was realized according to the method described by Abdouss and Sharifi-Sanjani. 17 According to this method, first PP and dodecanol-1 were mixed in an internal mixer (Brabender, Duisburg, Germany). Dried, filtered air was then put in contact with the molten mass at a flow rate of 1 L/min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in order to modify polypropylene to make it dyeable from aqueous dyebaths, a considerable research in recent years had been undertaken. Improving the dyeability of polypropylene fibres by means of chemical and physical modification methods inclusive of surface chemical reactions and functionalization, copolymerization and graft polymerizations, plasma and gamma radiation treatments, and blending of PP with polar polymers, metal compounds, inorganic nanoparticles, particularly, nanoclays, dendrimers and hyperbranched polymers, and many other additives has been widely investigated [ 5 13 ]. Considering economic, feasibility, and environmental aspects, it seems that melt blending with different kinds of polymeric additives such as polystyrene, polyamides, and polyesters, prior to spinning, could be an efficient process for the dyeability modification of PP fibers [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two peaks did not exist in the original PP, and all of the other peaks were similarly repeated. The absorbance at 1700–1780 cm −1 was related to the stretching mode of ketone, aldehyde, and anhydride carbonyl groups, and the peak at 3457 cm −1 was attributed to the stretching mode of OH groups in the alcohols 16. So, we concluded that the oxidation reaction proceeded through the formation of carbonyl and also alcohol functional groups.…”
Section: Resultsmentioning
confidence: 73%
“…The oxidation of PP was performed according the method described by Abdouss and Sharifi‐Sanjani 16. According to this method, first PP and dodecanol‐1 were mixed in an internal mixer (Brabender, Duisburg, Germany).…”
Section: Methodsmentioning
confidence: 99%